The concept of gamma-ray remote sensing of Martian surface composition onboard a Mars Rover. (October 2022) - Mitrofanov, Igor; Sanin, Anton; Litvak, Maxim; Golovin, Dmitry; Nikiforov, Sergey
Abstract: A novel concept of γ-ray remote sensing experiment onboard a Mars Rover is considered for studies of Martian shallow subsurface composition with a high spatial resolution. Only those photons produced in reactions of neutron inelastic scattering on nuclei of surface constituting elements are recorded by the proposed gamma-ray spectrometer, which use time tags of particles of Galactic Cosmic Rays (GCR), producing these reactions. It is shown that the composition of the Martian regolith may be determined by this gamma-ray spectrometer with a spatial resolution of meters along the traverse of a Mars Rover. Highlights: Numerical modeling is performed of experiments onboard a Rover for gamma-ray spectrometry of Martian subsurface. The new method of spectral data analysis is suggested to distinguish different types of Martian regolith. Gamma-ray spectrometer with time tags of GCRs has high sensitivity for local compositional variations of subsurface.